2017
DOI: 10.1016/j.bbr.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a probiotic supplementation on memory in quail suggests a role of gut microbiota on cognitive abilities in birds

Abstract: The gut microbiota is involved in host behaviour and memory in mammals. Consequently, it may also influence emotional behaviour and memory in birds. Quail from two genetic lines with different fearfulness (LTI: long tonic immobility, n=37; STI: short tonic immobility, n=32) were either or not supplemented with a probiotic (Pediococcus acidilactici) from hatching. Emotional reactivity was measured in a tonic immobility test (d6 and 7 of age) and two open-field tests (d13-15; d22-24). Memory was measured in a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Azeem (2013) showed that the administration of the probiotic Bacillus amyloliquefaciens helped to reduce distress calls and agonistic behaviour in turkeys. More recently, a decrease in emotional reactivity in a tonic immobility test and memory improvement have been described by Parois et al (2017) following continuous supplementation with the probiotic Pediococcus acidilactici in Japanese quails.…”
Section: Introductionmentioning
confidence: 99%
“…Azeem (2013) showed that the administration of the probiotic Bacillus amyloliquefaciens helped to reduce distress calls and agonistic behaviour in turkeys. More recently, a decrease in emotional reactivity in a tonic immobility test and memory improvement have been described by Parois et al (2017) following continuous supplementation with the probiotic Pediococcus acidilactici in Japanese quails.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the administration of the probiotic Bacillus amyloliquefaciens helped to reduce agonistic behavior and distress calls in turkeys (Azeem, 2013 ). More recently, it has been shown that continuous supplementation from hatching with a probiotic ( Pediococcus acidilactici) in Japanese quails caused a decrease in emotional reactivity in the tonic immobility test and improved memory (Parois et al, 2017 ). These results suggest that the gut microbiota is able to modify emotional behavior in poultry birds, as previously observed in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of the present study was to determine the effect of the absence of gut microbiota on emotional reactivity in birds by comparing germ-free to colonized quails, an experiment never before conducted in birds. The Japanese quail ( Coturnix japonica ), a precocial bird, was chosen as a model in this study due to its capacities to live without its mother in early life, thus limiting the influence of maternal microbiota, and also because the effects of a probiotic on emotional behavior of this bird have already been demonstrated in previous work from our laboratory (Parois et al, 2017 ). It was recently reported that the host's genetic could influence the effects of the gut microbiota on behavior (Crumeyrolle-Arias et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, germ-free mice colonized with microbiota from another mouse strain exhibit behavioural profiles of the donor strain 13 . The gut microbiota seems to have similar effects in poultry, where altering microbiota composition affects fearfulness, memory, and serotonergic and immune systems [14][15][16] . Moreover, microbiota transplantation to germ-free quails has resulted in recipients adopting the fearful behaviour of donors early in life; however, this effect reversed later Microbial groups for which the variation in relative abundance in the data is explained for at least 95% by the axes are represented as vectors.…”
mentioning
confidence: 99%